OPTIMALISASI KOMUNIKASI PEMERINTAHAN DINAS PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN MAROS DALAM PEMBINAAN DESA WISATA RAMMANG – RAMMANG DI KECAMATAN BONTOA - Rezki Pratama Putra , Andi; Zelfia, Zelfia; Muliadi, Muliadi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to examine the optimization of Communication Department of Tourism, Youth and sports as well as inhibiting and supporting factors in the development of Tourism Village. This study uses the method of quality description, with information in this study as many as eight (8) people, data collection techniques through observation, interviews and documentation. The development of Rammang – Rammang Tourism Village is to build image and cooperation by doing development to the tourism management community through training on improving human resources capacity to improve the welfare and prosperity of the community in managing a directed Tourism Village. The supporting and inhibiting factors are in the management of Rammang-Rammang tourism development as a geological park or geo park Maros-Pangkep, because Rammang-Rammang is the 2nd largest karst mountain area in the world.